Stability analysis of cellular structures made of flat metal sheet piles - E. M. Terikhov; A. S. Anshakov (Vestnik MGSU)
Introduction. Cellular structures are internationally used as temporary and permanent structures. They are made of interconnected sheet piles forming adjacent cells, and they are usually filled with backfilling soil. When cellular structures are used as coﬀerdams, massive cells (1) make the use of cement and mortar unnecessary and (2) allow for the foundation soil to be excavated to a shallow depth. Since there are practically no bending moments in sheet piles of cellular structures due to their shape and sheet piles are mainly in tension, flat sheet piles are used to make these structures.Materials and methods. In this study, stability of a cellular structure was analyzed in compliance with effective regulatory documents. Several values of (1) the diameter of sheet piles and (2) the sheet pile driving depth were selected to study and compare methods of stability analysis. In addition to stability, the safety factor of interlocks was found for all design sections. Analytically obtained results were compared with those computed in two- and three-dimensional settings using Midas FEA NX software package.Results. Graphs were made to demonstrate the dependence between stability factors, the depth and the diameter of a cellular structure. The results computed in two- and three-dimensional settings using Midas FEA NX software package were compared with those obtained using analytical methods of stability analysis.Conclusions. Results of numerical modeling made in the two-dimensional setting are similar to the analytical solution. They show a substantially smaller stability factor compared to the three-dimensional problem.